Determination of Polycyclic Aromatic Hydrocarbons in Mosses by Ultrasonic-Assisted Extraction and Gas Chromatography–Tandem Mass Spectrometry. (2nd January 2017) - Wu, Rangtian; Li, Na; Shu, Rong; An, Na; Yi, Feng; Yang, Wei; Li, Chongying
ABSTRACT: A facile method for the determination of polycyclic aromatic hydrocarbons in mosses is reported using ultrasonic-assisted extraction and gas chromatography–tandem mass spectrometry. The efficiency of ultrasonic-assisted extraction and the reagents was optimized. Tandem mass spectrometry with selective reaction monitoring was used to enhance the selectivity to reduce matrix interferences and simplify the purification protocol. The detection limits were from 0.1 to 2.0 ng/mL. The linear calibration range was two orders of magnitude and the coefficients of linear correlation exceeded 0.9992 for all analytes. The relative standard deviations within 1 day and 3 days were less than 9.0%. Recoveries from 56.8 to 109.0% were obtained in fortified mosses. The rapid, low solvent gas chromatography–tandem mass spectrometry method was used to determine polycyclic aromatic hydrocarbons in mosses.